Indigenous (traditional) vegetables as food and medicine in Adi community of East Siang (Pasighat), Arunachal Pradesh - Ramjan, Md.; Shankar, Kripa (Indian Horticulture, 2021)
The present investigation revealed only a fraction of traditional knowledge of plants used by the Adis of pasighat East Siang. An elaborate and long term study is required for understanding and documentation of traditional knowledge possessed by the Adi cummunity and its cultural connection. It is also important to conserve the language and the traditional lifestyle to foster the ethnic knowledge for the next generation.